The Effects of Cells Temperature Increment and Variations of Irradiation for Monocrystalline Photovoltaic - Faishal Fuad Rahman Soeharto; Hermawan Hermawan (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Photovoltaic cell technology has been developed to meet the target of 17% Renewable Energy in 2025 accordance with Indonesia Government Regulation No. 5 2006. Photovoltaic cells are made of semiconductor materials, namely silicon or germanium (p-n junction). These cells need the light that comes from solar irradiation which brings energy photons to convert light energy into electrical energy. It is different from the solar heater that requires heat energy or thermal of sunlight that is normally used for drying or heating water. Photovoltaic cells requires energy photons to perform the energy conversion process, the photon energy can be derived from sunlight. Energy photon is taken from the sun light along with the advent of heat due to black-body radiation, which can lead to temperature increments of photovoltaic cells. Increment of 1°C can decreased photovoltaic cell voltage of up to 2.3 mV per cell. In this research, it will be discuss the analysis of the effect of rising temperatures and variations of irradiation on the type monocrystalline photovoltaic. Those variation are analyzed, simulated and experiment by using a module of experiment. The test results show that increment temperature from 25° C to 80° C at cell of photovoltaic decrease the output voltage of the photovoltaic cell at 4.21 V, and it also affect the power output of the cell which decreases up to 0.7523 Watt. In addition, the bigger the value of irradiation received by cell at amount of 1000 W / m2, produce more output power cells at the same temperature.